Formulation and evaluation of tinidazole mucoadhesive buccal gels - S.GOUSIA BEGUM; Dr M.SEKAR (International Journal of Pharma and Bio Sciences, 2017)
In the present work mucoadhesive gels of Tinidazole that adhere with gums for an extended time period were prepared and evaluated. Tinidazole (TZ) is an antibacterial drug used for treatment of Periodontitis. Different gel formulations were prepared using the bio adhesive polymers like carbopol 974, sodium alginate and sodium carboxy methyl cellulose. The other additives used are triethanolamine as an emulsifier and surfactant, glycerol as a means of improving smoothness, providing lubrication and as humectants, mannitol as the isotonic agent and methylparaben as a preservative. The physicochemical compatibility of the drug and the polymer was assessed by FTIR spectroscopy. The prepared gels were evaluated for various parameters like viscosity, pH, drug content, swelling index, spread ability and Ex- Vivo drug permeation. Release of Tinidazole from the gels formulated by employing carbopol 974 extended the drug release up to 6hrs. So the formulations F7, F8, and F9 were found to be optimized formulae.